The Determinants of Household Risky Asset Holdings: Background Risk and Other Factors - Wilkins, R; Cardak, B (My University, 2008)
We study the portfolio allocation decisions of Australian households using the relatively new Household Income and Labour Dynamics in Australia (HILDA) survey. We focus on household allocations to risky financial assets. Our empirical analysis considers a range of hypothesised determinants of these allocations. We find background risk factors posed by labour income uncertainty and health risk are important. Credit constraints and observed risk preferences play the expected role. A positive age gradient is identified for risky asset holdings and homeownership is associated with greater risky asset holdings. A unifying theme for many of our empirical findings is the important role played by financial awareness and knowledge in determining risky asset holdings. Many non-stockholding households appear to lack the experience and financial literacy that might enable them to benefit from direct investment in stocks.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Finance; Finance -- Assets; Income, wealth and finances; Income, wealth and finances